Benefits and problems in caged rearing of Lates calcarifer, Oreochromis niloticus and Pangasius sutchi: the case of entrepreneurs in Pekan, Pahang - Idris, Khairuddin; Azman, Azmariana; Alby, Jeffrey Lawrence D'Silva; Man, Norsida; Mohamed Shaffril, Hayrol Azril (Marsland Press, 2013)
As marine sources are consistently depleting, turning to aquaculture as an alternative source is seen as a vital step. However, little academic interest has been paid to aquaculture, particularly the social part of it. This study aims to identify the benefits and problems faced by entrepreneurs in Pekan Pahang who run caged aquaculture activities, particularly regarding three species: Lates calcarifer (sea bass), Oreochromis niloticus (red tilapia) and Pangasius sutchi (patin). To gain the required data, two Focus Group Discussions are conducted using a total of 12 respondents; five respondents in Tanjong Gosong and seven respondents in Pulau Keladi Village in Malaysia. In terms of the benefits of aquaculture activities, four main themes emerge, namely increasing their income, a sense of hard work, creatively solving problems and creating a norm of cooperation. In terms of problems faced by the entrepreneurs, four main themes emerge, namely relating to financial, environmental, seedling and diseases, and human and animal factors.